Analisis Fasilitas Penunjang Sektor Pariwisata di Bandara Sisingamangaraja XII dalam Mendukung Kawasan Danau Toba Sebagai Destinasi Super Prioritas - Putri Ayu Andriani Simanjuntak (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
This study aims to assess the quality and impact of supporting tourism facilities at Sisingamangaraja XII International Airport in strengthening the development of Lake Toba as a Super Priority Destination. The airport holds a strategic role as the main gateway for tourists visiting the Lake Toba area, making the quality of services and the completeness of facilities crucial aspects in creating a memorable travel experience. The research employed a qualitative approach with data collected through in-depth interviews with key informants, direct field observations, and documentation. Data analysis was conducted using the (SERVQUAL) model, which evaluates five key dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The findings reveal that the airport has provided several tourism-supporting facilities, including ground transportation services, food and beverage outlets, as well as souvenir and gift shops. However, the implementation of these facilities has not yet reached optimal performance. Identified challenges include the limited choice of transportation options to and from various tourist destinations, the lack of authentic Lake Toba culinary offerings at food and beverage outlets, and the insufficient promotion of local products at souvenir shops. Furthermore, the absence of essential services such as travel agencies and money changers has negatively affected convenience, particularly for international tourists who require accessible information, transactions, and travel services. These findings indicate that improving supporting facilities at Sisingamangaraja XII International Airport is an urgent necessitySuch efforts are expected to enhance the quality of airport services, increase tourist satisfaction, and ultimately reinforce Lake Toba’s position as a leading national and international tourism destination.